2010
DOI: 10.1007/s00059-010-3360-0
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of the vascular compartment

Abstract: Throughout life, damage to the vascular endothelium is pivotal in the development of cardiovascular disease. Therefore, a detailed understanding of the underlying mechanisms involved in endothelial cell restoration is of fundamental importance for preventive and therapeutic concepts in cardiovascular disease. The goal of regenerative medicine is the use of tissue-specific progenitor cells for a more effective repair process with reduction of fibrocellular remodelling, fibrosis and loss of functional properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 62 publications
0
14
0
1
Order By: Relevance
“…Interestingly, further studies associated the presence/absence of surface markers with specific functionalities of EPCs, like vascular homing and repair competence, incorporation into the damaged endothelium, and in vivo vessel formation (Asahara et al, 1997;Becher et al, 2010;Friedrich et al, 2006;Hur et al, 2004;Sieveking et al, 2008).…”
Section: The Role Of Endothelial Progenitor Cells In Vascular Integritymentioning
confidence: 99%
“…Interestingly, further studies associated the presence/absence of surface markers with specific functionalities of EPCs, like vascular homing and repair competence, incorporation into the damaged endothelium, and in vivo vessel formation (Asahara et al, 1997;Becher et al, 2010;Friedrich et al, 2006;Hur et al, 2004;Sieveking et al, 2008).…”
Section: The Role Of Endothelial Progenitor Cells In Vascular Integritymentioning
confidence: 99%
“…Moreover, we find that HFD appears to decrease the proliferation of tissue-resident cells, suggesting that, these resident EPCs might have decreased proliferative capacity and contribute to pathological adipose tissue remodeling. This is important because decreased levels of these pro-angiogenic cells have been implicated in the development of several chronic diseases including cardiovascular disease, due likely to a diminished capacity to repair damaged vasculature (73)(74)(75)(76)(77)(78). Obesity along with exposure to other environmental factors, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Levels of these cells can be influenced not only by obesity, but by several environmental factors such as exposure to air pollution and components of cigarette smoke (68,69,71,72 (68,69,71,(80)(81)(82). Taken together, it can be concluded that EPCs function to repair damaged vasculature in order to maintain adequate tissue oxygenation, preventing further ischemia-induced cell death and fibrosis (75). Interestingly, the term "EPC" is a general one describing a variety of cell types that have been shown to promote angiogenesis or vessel repair (68,69,71,75,80,82 …”
Section: Specific Cells Of Interestmentioning
confidence: 99%
See 2 more Smart Citations